Changes in Glucose and Glutamine Lymphocyte Metabolisms Induced by Type I Interferon α. (27th December 2010) - Navarro, Francisco; Bacurau, Aline V. N.; Vanzelli, Andréa; Meneguello-Coutinho, Marcela; Uchida, Marco C.; Moraes, Milton R.; Almeida, Sandro S.; Wasinski, Frederick; Barros, Carlos C.; Würtele, Martin; Araújo, Ronaldo C.; Costa Rosa, Luís F. B.; et al.
Abstract : In lymphocytes (LY), the well-documented antiproliferative effects of IFN-α are associated with inhibition of protein synthesis, decreased amino acid incorporation, and cell cycle arrest. However, the effects of this cytokine on the metabolism of glucose and glutamine in these cells have not been well investigated. Thus, mesenteric and spleen LY of male Wistar rats were cultured in the presence or absence of IFN-α, and the changes on glucose and glutamine metabolisms were investigated. The reduced proliferation of mesenteric LY was accompanied by a reduction in glucose total consumption (35%), aerobic glucose metabolism (55%), maximal activity of glucose-6-phosphate dehydrogenase (49%), citrate synthase activity (34%), total glutamine consumption (30%), aerobic glutamine consumption (20.3%) and glutaminase activity (56%). In LY isolated from spleen, IFNα also reduced the proliferation and impaired metabolism. These data demonstrate that in LY, the antiproliferative effects of IFNα are associated with a reduction in glucose and glutamine metabolisms.